Hestnes Ferreira between european timelessness and north american classicism - Saraiva, A. (2020)
Raúl Hestnes Ferreira (1931-2018) belonged to the fourth generation of modern Portuguese architects who received their diploma between the 1940s and 1950s. After graduation, his experiences, studies, and surveys made him a unique character among his fellows and a key-figure to understand the national debate, particularly in the second half of the 20th century. This article aims to emphasize the importance of staying in the United States as a student and architect, having Louis Kahn as his most excellent teacher, which was crucial to his career as an architect in Portugal. The American experience allowed Hestnes Ferreira to understand the significance of the ancient Mediterranean culture and the extension of the idea of ‘monumentality’ according to Kahn's thoughts. After returning to Portugal, in 1967, this awareness was crucial to develop architecture conceived from conventional technological processes, sensitive to accessible knowledge, to place, matter, and proportion, providing to a certain extent the restoration of some social foundations of architecture. The article, based on ongoing postdoctoral research, which aims to study Hestnes Ferreira’s archive, donated to the Marques da Silva Foundation Institute (FIMS).